Effectiveness of Perineal Massage in the Second Stage of Labor in Preventing Perineal Trauma - Suleyman Cemil Oglak; Mehmet Obut (Gynecology Obstetrics & Reproductive Medicine, 2020)
OBJECTIVE: This study was aimed to investigate the effect of perineal massage in the second stage of labor in prevention perineal traumas during childbirth.